D24 Intact emotional impulsivity in huntington's disease despite altered structural connectivity in the uncinate fasciculus. (13th September 2016) - Marco-Garcia, Silvia; Garcia-Gorro, Clara; Orpella-Garcia, Joan; Rodriguez-Dechicha, Nadia; Martinez-Horta, Saül; Vaquer, Irene; Calopa, Matilde; Perez, Jesus; Muñoz, Esteban; Santacruz, Pilar; Ruiz, Jesus M; Mareca, Celia; et al.
Abstract : Background: Impulsivity in Huntington's disease (HD) patients has been understudied despite its clear impact in daily life. Although it is known that there are different types of impulsivity, this trait has been mainly studied through impulsive actions in cued go/no-go tasks that contain an important motor component, while the more purely emotional/choice component of impulsivity in HD remains unknown. Objective: To study the neurobiological basis that characterise individual differences in emotional impulsivity in HD. Methods: Thirty-one controls and 32 HD patients (11 of which were pre-symptomatic) were scanned using diffusion tensor imaging (DTI) to study the relationship between the structural connectivity of the uncinate fasciculus (UF), the main tract involved in the motivational circuit, and the impulsivity trait (k), evaluated with a delay discounting task. Results: No significant difference was observed in k between the two groups. In controls, k correlated with both right and left UF, whereas in HD patients, k correlated only with the left UF. On the other hand, only the right UF was found to be affected in HD patients compared with controls. Conclusion: This study reveals that HD patients do not differ from controls in the impulse behaviour associated with delay discounting choices. Moreover, the connectivity pattern observed in HD patients and controls is consistent with previous studies that show that individual differences in microstructure integrity of the left UF are related to impulsivity levels in delay discounting tasks.